Teacher-Child Interactions in Infant and Toddler Classrooms: A Qualitative Study Examining the Nature of Care - Stubblefield, Jessica (My University, 2015)
The purpose of this study was to describe and explore the nature of infants’, toddlers’, and caregivers’ lived experiences in group care settings. Multi-case qualitative research was conducted with three infant and/or toddler caregivers in high quality centers. Observations closely examined the interactions infants and toddlers had with caregivers, and interviews were conducted to explore the caregivers’ perceptions. There were four research foci explored: the nature of the lived experience for infants and toddlers in high quality group care settings, the ways in which infants and/or toddlers sent bids to their caregivers for support, the ways in which caregivers responded to infants’ and/or toddlers’ bids, and the ways caregivers perceived their role of caring. Teacher-child interactions were qualitatively documented to gain organized information regarding what was occurring. Three major findings include: 1) the impact of aggression on caregiver-child interactions, as well as caregiver focus and attention, 2) how teacher breaks and time away from the children’s presence impact caregiving relationships, and 3) caregivers who engaged in warm and reliable caring interactions fostered optimal relational bonds in which children were observed sending more bids for support when help was needed. Additionally, even though all three caregivers shared the belief that care should be individualized and unique to the child and situation occurring in the moment, caregiver perceptions of respect and sensitivity were rather varied in actual practice. Findings are discussed in terms of implications for future research, policy, and practice.
Keywords: teacher-child interactions, secure base, sensitivity, responsiveness